'Just accept each other, while the rest of the world doesn't' –teachers' reflections on multilingual education. (3rd September 2022) - Duarte, Joana; Günther-van der Meij, Mirjam
Abstract: Research suggests that in linguistically and socially diverse classrooms, teachers should draw on their students' multilingual repertoires. Although several approaches to use students' home languages exist, the accessibility of this knowledge among teachers is still limited. Recently, a holistic approach has been put forward to address the needs of teachers in navigating the jungle of available knowledge. Within two projects in the Netherlands the approach was tested to develop multilingual approaches. Using data from vignettes applied after a two-year intervention period, this paper first explores knowledge, attitudes and skills developed by the participating teachers on implementing forms of multilingual education. Next, it analyses interaction data by applying a critical discourse analysis to filter out how othering strategies occur when teachers refer to their linguistically and culturally diverse students. The results show that the teachers mostly hold enhancing attitudes, particularly in terms of using the students' home languages in class, while othering strategies towards multilingual students only rarely occur. This may highlight the importance of professional development for teachers-in-duty, and allows for valuable insights also for other schools who wish to engage in multilingual education.